2010
DOI: 10.1038/aps.2010.87
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae and caveolin-1 mediate endocytosis and transcytosis of oxidized low density lipoprotein in endothelial cells

Abstract: Aim: To explore the mechanisms involved in ox-LDL transcytosis across endothelial cells and the role of caveolae in this process. Methods: An in vitro model was established to investigate the passage of oxidized low density lipoprotein (ox-LDL) through a tight monolayer of human umbilical vein endothelial cells (HUVEC) cultured on a collagen-coated filter. Passage of DiI-labeled ox-LDL through the monolayer was measured using a fluorescence spectrophotometer. The uptake and efflux of ox-LDL by HUVEC were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…Using fibroblasts derived from c-Abl or Src knock-out mice, Sanguinetti and Mastick (19) showed that c-Abl phosphorylates caveolin-1 independently of Src. In contrast, in pulmonary microvascular endothelial cells, Sun et al (2,20,38) reported that c-Abl activation and subsequent caveolin-1 phosphorylation is in part dependent on Src activity. They further mentioned that the c-Abl pathway becomes more important particularly when higher concentrations of H 2 O 2 are used to stimulate caveolin-1 phosphorylation.…”
Section: Discussionmentioning
confidence: 95%
“…Using fibroblasts derived from c-Abl or Src knock-out mice, Sanguinetti and Mastick (19) showed that c-Abl phosphorylates caveolin-1 independently of Src. In contrast, in pulmonary microvascular endothelial cells, Sun et al (2,20,38) reported that c-Abl activation and subsequent caveolin-1 phosphorylation is in part dependent on Src activity. They further mentioned that the c-Abl pathway becomes more important particularly when higher concentrations of H 2 O 2 are used to stimulate caveolin-1 phosphorylation.…”
Section: Discussionmentioning
confidence: 95%
“…CAV1 potentially plays an important positive role in the regulation of LSEC tubular formation (Yokomori et al 2009). Recent studies demonstrate that CAV1 expression increases oxLDL uptake by hepatic cells and mediates oxLDL endocytosis and transcytosis by ECs (Truong et al 2009, Sun et al 2010. Furthermore, oxLDL upregulates CAV1 expression and downregulates eNOS expression at the mRNA and protein levels in HUVECs (Ma et al 2012).…”
Section: Figurementioning
confidence: 99%
“…Recently, we found that caveolae and caveolin-1 mediate the endocytosis and transcytosis of oxidized low-density lipoprotein (ox-LDL) in endothelial cells [10] . Caveolae in the plasma membrane may invaginate and form caveolar vesicles that contain cholesterol or lipoprotein.…”
Section: Model Of Reverse Cholesterol Transportationmentioning
confidence: 99%